2020
DOI: 10.3892/ijmm.2020.4737
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circularRNA_0079201 suppresses chondrocyte proliferation and endochondral ossification by regulating the microRNA‑140‑3p/SMAD2 signaling pathway in idiopathic short stature

Abstract: Circular (circ)RNAs are an important group of non-coding RNAs involved in different pathological and physiological functions, such as longitudinal bone growth. However, the effects of an increase or decrease in circRNA expression on idiopathic short stature (ISS) remain largely unknown. The present study compared the circRNA expression patterns of patients with ISS and healthy individuals to identify differentially expressed circRNAs involved in the regulation of ISS pathogenesis and their target microRNAs (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…One of the circRNAs that was highly expressed in ISS, circRNA_0079201, functions as an miR-140-3p sponge. Furthermore, the proliferation, hypertrophy, and endochondral ossification of chondrocytes in ISS are regulated by the hsa_circRNA_0079201/miR-140-3p/SMAD2 pathway [ 129 ].…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…One of the circRNAs that was highly expressed in ISS, circRNA_0079201, functions as an miR-140-3p sponge. Furthermore, the proliferation, hypertrophy, and endochondral ossification of chondrocytes in ISS are regulated by the hsa_circRNA_0079201/miR-140-3p/SMAD2 pathway [ 129 ].…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…To determine the role of circRNAs in the molecular mechanisms of ISS, researchers identified differential expression of circRNAs in the peripheral blood of patients with ISS versus healthy controls. According to the outcomes of the circRNAs microarray, 145 differentially expressed circRNAs were screened (83 upregulated and 62 downregulated) ( Liu et al, 2020 ; Liu et al, 2021 ). In subsequent studies, it was verified that circANAPC2 and hsa_circularRNA_0079201 can serve as potential targets for treatment of ISS ( Liu et al, 2020 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the outcomes of the circRNAs microarray, 145 differentially expressed circRNAs were screened (83 upregulated and 62 downregulated) ( Liu et al, 2020 ; Liu et al, 2021 ). In subsequent studies, it was verified that circANAPC2 and hsa_circularRNA_0079201 can serve as potential targets for treatment of ISS ( Liu et al, 2020 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of short stature is pathological, and 80% is idiopathic due to unknown causes (16). Factors associated with less height gain have been extensively evaluated, yet the results are not often reproducible, especially for modifiable factors (17,18). For example, some studies have showed that high body mass index (BMI) was positively associated with short stature and pre-shortness (13,20), whereas others failed to support this claim (21).…”
Section: Introductionmentioning
confidence: 99%